2003
DOI: 10.1007/s00775-003-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Could the tyrosine-histidine ligand to CuB in cytochrome c oxidase be coordinatively labile? Implications from a quantum chemical model study of histidine substitutional lability and the effects of the covalent tyrosine-histidine cross-link

Abstract: Density functional theory calculations have been used to evaluate the effects of inter-ring interactions within a covalently linked histidine-tyrosine cofactor such as that which is a ligand to the Cu(B) centre in cytochrome c oxidases and to investigate the energetics of histidine substitution at the Cu(B) centre. Small, but significant, perturbations of the redox potentials and/or p K(a) values of the histidine imidazole, the tyrosine phenol and the copper ion are found. The Cu(B)-N(cofactor) bond is estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…In the corresponding UV–vis spectra, such slight changes in the coordination sphere of (bpy)­Cu II (NMI) are reflected by a small change in the d–d band when more than 1.0 equiv of NMI is added (Figure B). This indicates weak coordination of an additional NMI molecule and is in accordance with the fact that IM-type ligands are known as labile ligands in biological systems. The labile coordination of NMI to the Cu I center may be of vital importance for electron transfer from Cu I to O 2 because one coordinating NMI ligand is supposed to be temporarily displaced from the Cu center to enable O 2 adsorption and subsequent superoxide formation. From in situ IR measurements at −40 °C, we obtained experimental support that this may indeed happen (Figure S7).…”
Section: Resultssupporting
confidence: 52%
“…In the corresponding UV–vis spectra, such slight changes in the coordination sphere of (bpy)­Cu II (NMI) are reflected by a small change in the d–d band when more than 1.0 equiv of NMI is added (Figure B). This indicates weak coordination of an additional NMI molecule and is in accordance with the fact that IM-type ligands are known as labile ligands in biological systems. The labile coordination of NMI to the Cu I center may be of vital importance for electron transfer from Cu I to O 2 because one coordinating NMI ligand is supposed to be temporarily displaced from the Cu center to enable O 2 adsorption and subsequent superoxide formation. From in situ IR measurements at −40 °C, we obtained experimental support that this may indeed happen (Figure S7).…”
Section: Resultssupporting
confidence: 52%
“…Furthermore, their computational data are consistent with our previous experimental observation 10 that formation of a phenoxyl radical results in a significant decrease in the basicity of the coordinating imidazole imino nitrogen. 25 To date, no experimental or theoretical studies have focused on the influence of phenolate formation on the coordination chemistry of an imidazole-phenol ligand bound to a divalent metal ion via the imidazole. The present study was directed towards understanding the role of a metal ion in perturbing the physicochemical properties (pK a , oxidation potential) of the cross-linked phenol, and its corresponding aqueous coordination chemistry as a function of pH, in complexes that maintain the dihedral angle observed in the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the redox state and protonation state of the tyrosine influence the electron donating capacity of the imidazole as a metal ligand, thus controlling the preferred ligand geometry about Cu B (35). It has also been suggested that, due to the presence of the crosslinked tyrosine, the histidine ligand to Cu B might be labile and move away from the metal during turnover, playing a key role in the proton pump mechanism (40). These studies, in conjunction with the presence of the crosslinked cofactor in all oxygen reductase families, suggests that the cofactor may be a required component for proton pumping.…”
Section: The Functional Role Of the His-tyr Crosslinkmentioning
confidence: 99%
“…Recent studies with model compounds (35)(36)(37)(38)(39) as well as computational studies (26,40) have suggested a possible functional significance for the crosslink. The crosslinked histidine withdraws electrons from the tyrosine, resulting in a lower pKa and a higher midpoint potential of the tyrosine (41).…”
Section: The Functional Role Of the His-tyr Crosslinkmentioning
confidence: 99%